Um estudo descritivo-analítico da gramática metódica da língua portuguesa e do dicionário de questões vernáculas de Napoleão Mendes de Almeida - Borges, Juliana Marítimo (2008)
This thesis is in the research line of Portuguese Language s History and Description. Its subject of study is formed by two works, to wit, Gramática Metódica da Língua Portuguesa (Portuguese Language Methodic Grammar) and Dicionário de Questões Vernáculas (Dictionary of Vernacular Issues), both written by Napoleão Mendes de Almeida, with in the scope of the contextual movements in which such books were produced. This research main purpose is looking for answers for the author s conservative and nationalist, together with his desire to preserve the traditional Portuguese grammar. Particularly: 1) depicting the political, social, economic, and cultural moment in which the author had his higher production: the Vargas Age (from 1930-45, and 1951-54, with deep socioeconomic changes in Brazil); 2) analyze Gramática Metódica, and Dicionário as mentioned above. The importance of this essay is justified by the author s posture, deeply rooted in conservative theories, keeping himself resistant to theoretical innovations of his time. This research is grounded on the theoretical presuppositions of the Linguistic Ideas History. As regards its purposes, the results obtained pointed out that, in said works, the Brazilian historical and political moment influenced the author's conservative and nationalist; accordingly, the goals were satisfactorily achieved. The methodological procedure used was the theoretical-descriptive and deductive, for the steps followed were efficient to guide the search for answers on the presented purposes. Notwithstanding, it can be concluded that this research has to continue, because the investigation carried out focused only two works of Napoleão Mendes de Almeida